A manifesto for 'slow' comparative research on work and employment. (March 2020) - Almond, Phil; Connolly, Heather
We offer a defence of, and framework for, comparative research in industrial and employment relations, based on a long-term engagement with the social contexts under study. We locate 'slow' research strategies in relation to predominant approaches and establish a number of basic precepts of slow comparativism as a practical methodological approach. We aim to provoke a discussion among those conducting comparative research on work and employment about how truth claims are generated. We also seek a basis by which those conducting slower forms of comparativism, through what we term 'implicit ethnographies', can find better ways of developing and defending their modes of research within an often hostile academic political economy.